Answers

2015-06-29T12:44:33+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Use those formulas
in LHS, mlog(n) = log (n^m)
in rhs, logx +logy= log (xy)
if you are still having problems, feel free to ask.. :)

lhs
2log(x+y)= log((x+y)^2) = log( x^2+y^2+2xy)= log(25xy+2xy)=log(27xy)= log27 + logxy= 3log3 +logxy
hence, proved
0